Rekonstruksi Teologi Kritis Berbasis Humanistik–Eksistensial: dari Krisis Normativitas Menuju Teologi Emansipatoris-Transformatif - Farikha Aula Khoirina; Nayla Izzati Qolbi; Yasierly Amria; Mohammad Hakim; Ali Hasan Siwanto (Indo Publishing, 2026)
The academic crisis in contemporary theological studies stems from the dominance of normative paradigms that tend to be scripturalistic, legalistic, and insufficiently responsive to the existential problems of modern humanity. As a result, theology experiences functional disorientation, failing to address crises of meaning, spiritual alienation, and the individual’s need for self-actualization. Although critical theology discourse has developed, there remains a research gap in the form of minimal systematic integration between theological approaches and humanistic–existential psychology, particularly in understanding religiosity as a lived experience. This study aims to reconstruct the paradigm of critical theology based on a humanistic–existential approach by referring to the theoretical framework of Abraham Maslow, especially the concepts of hierarchy of needs, self-actualization, and peak experience. The method employed is qualitative-conceptual research using an interdisciplinary approach that combines theological, philosophical, and psychological analysis through critical analysis techniques and hermeneutic synthesis. The main argument of this article asserts that theology needs to be repositioned from merely a system of normative doctrines toward an existential praxis that is humanizing, dialogical, and transformative. The integration of humanistic psychology enables theology to become more responsive to the inner dynamics of human beings and to function as a medium for the emancipation of spiritual consciousness. The scientific contribution of this research lies in the formulation of an emancipatory-transformative theological paradigm based on human existential experience, while also offering an integrative model between critical theology and humanistic–existential psychology that enriches the discourse of contemporary Islamic scholarship